2022
DOI: 10.1002/pri.1941
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of musculoskeletal pain in patients with dizziness—A systematic review

Abstract: Background and purpose: Musculoskeletal disorders are among the leading causes of disability globally, but their role in patients with dizziness and imbalance is not well understood or explored. Such knowledge may be important as musculoskeletal pain and dizziness can mutually influence each other, leading to a complex condition requiring more comprehensive approaches to promote successful recovery. We conducted a systematic review to examine the extent and characteristic of reported musculoskeletal pain in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(144 reference statements)
3
4
0
Order By: Relevance
“…The pattern of pain localization, where the neck, back, and shoulders are the most reported pain sites, is similar to what reported in other studies on patients with dizziness [17,34] and in the general population [26,32]. However, the frequency was markedly higher in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The pattern of pain localization, where the neck, back, and shoulders are the most reported pain sites, is similar to what reported in other studies on patients with dizziness [17,34] and in the general population [26,32]. However, the frequency was markedly higher in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of pain reported in our study is in line with other studies on patients with dizziness [10,17,18]. Despite that estimates of pain prevalence may vary between studies due to differences in methodology, definitions, and context, the prevalence in the current study was substantially higher than in the general population in Norway (94.5% versus 25%) [30,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Association between pain intensity as the dependent variable, and dizziness symptoms, dizziness-related handicap, or dizziness catastrophizing thoughts as independent variables, examined with linear regression analysis.The high prevalence of pain reported in our study is in line with other studies on patients with dizziness(Gustavsen et al, 2021;Malmström et al, 2021;Moen et al, 2022). Despite that estimates of pain prevalence may vary between studies due to differences in methodology, de nitions, and context, the prevalence in the current study was substantially higher than in the general population in Norway (94.5% versus 25%) (Kinge, Knudsen, Skirbekk, & Vollset, 2015;Rustøen et al, 2004).…”
supporting
confidence: 89%
“…However, neck pain is also found to be part of a widespread pain pattern in the general population (Natvig, Ihlebaek, Grotle, Brage, & Bruusgaard, 2010), and this could probably apply to dizziness populations as well. A recent systematic review found that pain in other body parts is also evident in patients with dizziness (Moen et al, 2022), and dizziness is further found to be associated with local as well as widespread pain (Gustavsen et al, 2021). It is possible to speculate that both dizziness and pain could have a mutual preserving effect on each other as both symptoms could result in a more rigid movement pattern, leading to increased muscular tension and reduced recovery from dizziness (Coelho Júnior et al, 2010;Wilhelmsen & Kvåle, 2014).…”
Section: Introductionmentioning
confidence: 99%